A national survey of asthma prevalence, severity, and treatment in Great Britain. Issue 3 (March 1994) - Strachan, D P; Anderson, H R; Limb, E S; O'Neill, A; Wells, N
Abstract : Parents of 5472 children aged 5-17 years from 3209 families were interviewed in a nationwide household survey. In the past year, 15.0% of children had wheezed, 2.2% had more than 12 attacks, and 2.3% had experienced a speech limiting attack. Altogether 4.3% were woken more than once a week by wheezing, 13.1% had doctor diagnosed asthma, and 13.6% had been prescribed antiasthmatic drugs in the past year. With increasing age, morbidity related to wheezing declined to a greater extent than annual period prevalence. The prevalence of wheeze varied little by socioeconomic group, but there were marked trends in all three indices of severity towards increased morbidity in poorer families. Diagnostic labelling and drug treatment of wheezy children did not differ substantially with socioeconomic status. Thus, a degree of socioeconomic equality exists in the process of medical care for childhood asthma in Britain. This does not appear to have resulted in equality of outcome.